Obtaining Pacs from Cellulose of Sunflower Plants, Saflor and From Waste of The Textile Industry - M.K. Urozov; O. A. Toshbekov; O.Х. Кulmuminov; I.B. Boltayeva (Zien Journals, 2021)
At the end of the cellulose synthesis, sedimentary NaOH contains lignin, which contains various functional groups such as phenol, benzene, hydroxide, carbonyl, and functional groups that absorb heat. These functional groups in the composition of lignin have been used as an inhibitor in the preparation of the PAC ether, and positive results have been obtained.
Keywords: Cellulose; Na-CMC; product; PAC